Experimental and numerical investigation of low-temperature performance of modified asphalt binders and mixtures. Issue 6 (2nd November 2017) - Jahanbakhsh, H.; Karimi, Mohammad M.; Tabatabaee, Nader
Abstract : Thermal cracking is the prevalent type of distress experienced by asphalt pavements in cold regions. It is widely assumed that when thermal stresses induced in the pavement exceed the tensile strength of the asphalt surface layer, cracking occurs; however, the role of thermal fatigue should not be ignored. To better describe the low-temperature (LT) performance properties of modified asphalt binders, a new parameter, normalised tensile stress (NTS), was defined in this research. NTS values were compared with bending beam rheometer (BBR), direct tension (DT) and semi-circular bending (SCB) fracture test results. The m -value parameter of the BBR test specifies the type of asphalt binder. This classification changes as the loading time changes and is only valid in the linear viscoelastic range. It showed limited sensitivity to changes in the material properties of modified asphalt binders that showed superior LT damage resistance. In contrast, the results from the DT, SCB and NTS parameters were sensitive to the changes. The results of SCB testing and NTS parameters were in agreement with the existing field data. It was also found that the use of sulphur as a cross-linking agent improved the storage stability of styrene butadiene styrene (SBS)-modified asphalt binder and decreased the amount of SBS required to yield a comparable result by about 50%. In contrast to what has been reported by some investigators, the use of polyphosphoric acid as a cross-linking agent intensified the phase separation of bitumen and SBS, and somewhat reduced the efficacy of SBS modification with regard to LT performance.